Endometriotic inflammatory microenvironment induced by macrophages can be targeted by niclosamide. Issue 2 (16th October 2018) - Sekulovski, Nikola; Whorton, Allison E; Shi, Mingxin; MacLean, James A; Hayashi, Kanako
Abstract: Endometriosis causes severe chronic pelvic pain and infertility. We have recently reported that niclosamide treatment reduces growth and progression of endometriosis-like lesions and inflammatory signaling (NF${\rm \small K}$ B and STAT3) in a mouse model. In the present study, we examined further inhibitory mechanisms by which niclosamide affects endometriotic lesions using an endometriotic epithelial cell line, 12Z, and macrophages differentiated from a monocytic THP-1 cell line. Niclosamide dose dependently reduced 12Z viability, reduced STAT3 and NF${\rm \small K}$ B activity, and increased both cleaved caspase-3 and cleaved PARP. To model the inflammatory microenvironment in endometriotic lesions, we exposed 12Z cells to macrophage conditioned media (CM). Macrophages were differentiated from THP-1 cells using 12-O-tetradecanoylphorbol-13-acetate as M0, and then M0 macrophages were polarized into M1 or M2 using LPS/IFNγ or IL4/IL13, respectively. Conditioned media from M0, M1, or M2 cultures increased 12Z viability. This effect was blocked by niclosamide, and cell viability returned to that of CM from cells treated with niclosamide alone. To assess proteins targeted by niclosamide in 12Z cells, CM from 12Z cells cultured with M0, M1, or M2 with/without niclosamide were analyzed by cytokine/chemokine protein array kits. Conditioned media from M0, M1, and/or M2 stimulated the secretion of cytokines/chemokines from 12Z cells. Production of most of these secreted cytokines/chemokines in 12Z cells was inhibited by niclosamide. Knockdown of each gene in 12Z cells using siRNA resulted in reduced cell viability. These results indicate that niclosamide can inhibit the inflammatory factors in endometriotic epithelial cells stimulated by macrophages by targeting STAT3 and/or NF${\rm \small K}$ B signaling. Abstract : Niclosamide can inhibit the inflammatory microenvironment established between endometriotic epithelial cells and macrophages by targeting STAT3 and NFκB signaling.